Perjuangan Pengakuan Hak Kelola Lahan bagi Pengungsi Aceh di Kawasan Taman Nasional Gunung Leuser - Doni Latuparisa; Suraya Abdulwahab Afiff (Umbara, 2021)
Gunung Leuser national park covers an area of 830,268.95 hectares which has been designated as a national park since 1980. It has been managed by the Indonesian government through Gunung Leuser National Park Center. Ecological zonation systems have been implemented in the management. However, since about 1999, groups of refugees who escaped from the Aceh conflict have resided in the national park. They transformed the dry or bush landscape which is designated for conservation area into settlements, as well as rubber and oil palm plantations. The national park authority considers their activities illegal. While the refugees, after 20 years of their activities in the park, consider themselves to have the rights to cultivate the land.  They have attempted various ways to legalize their settlement and right to cultivate the area inside the park. This qualitative study aims at describing the tenurial conflict faced by refugees residing in the Gunung Leuser national park. Data were collected through interviews and participant observation. The study found the violence and harsh tension in regards to this tenurial conflict. On one hand, the refugees fight for their livelihood in the park. On the other hand, the park management tends to implement their authority to assure the original function of the national park. The government should take necessary action to resolve this long-term conflict using a rights-based approach; so the refugees, who are also the citizens of the state, could have their access to cultivate the land.